A comparative study on the NH3 gas-sensing properties of ZnO, SnO2, and WO3 nanowires. (24th January 2011) - Hieu, Nguyen Van; Le, Dang Thi Thanh; Khoang, Nguyen Duc; Quy, Nguyen Van; Hoa, Nguyen; Tam, Phuong; Le, Anh-Tuan; Trung, Tran
In this work, a large quantity of ZnO, SnO2 and WO3 nanowires (NWs) was successfully synthesised by simple and efficient methods. Their morphology and microstructure were characterised by FE-SEM, TEM, XRD, PL, and Raman. The NH3 gas-sensing properties of these NWs were investigated and compared. It was found that the responses and response-recovery time of SnO2 and WO3 NWs sensors to NH3 gas are relatively comparable, and they have a better NH3 gas-sensing performance than that of ZnO NWs sensor. In addition, the SnO2 NWs sensor has the lowest operating temperature.